Trophic Ulcer Elimination in Free Flap Reconstructed Weight-Bearing Plantar Defect: A Clinical Challenge - Lin, Chih-Hung; Lin, Cheng-Hung; Hsu, Chung-Chen (Seminars in Plastic Surgery, 2025)
Trophic ulceration represents a significant complication following free flap reconstruction of the plantar surface. Despite successful microvascular tissue transfer for posttraumatic defects, these ulcers develop due to biomechanical incompatibility, sensory deficits, and altered pressure distribution. This review examines the multifaceted pathophysiology of trophic ulcers in reconstructed plantar surfaces, comparing tissue characteristics across different flap options and exploring evidence-based preventive and management strategies. Understanding the biomechanical principles, including friction forces, shear stress, and viscoelastic properties, is crucial for optimizing surgical planning and postoperative care to reduce ulceration risk and preserve long-term foot function.
Keywords: trophic ulcer; free flap; plantar reconstruction; sensory loss; microsurgery